Drugs, crime, and their relationships : theory, research, practice, and policy - Walters, Glenn D. (xv, Sudbury, Massachusetts : Jones & Bartlett Learning, 2014)
Surveys administered to high school students, studies carried out on jail and prison inmates, and interviews conducted with substance abusers undergoing treatment all point to the same conclusion: drugs and crime are strongly connected. Why they are connected is less well understood, however. Written for middle to upper-level undergraduate courses on drugs and crime or substance abuse and crime, this book examines the drug-crime connection in a systematic and comprehensive way. This book covers the entire drug-crime spectrum, starting with a review of drug and crime terminology, classification and theory, and ending with policy implications for prevention, harm reduction, and macro-level management of the drug-crime problem. The opening chapters discuss drugs and crime separately for the purpose of setting the stage for later discussions on drug-crime relationships. As the book proceeds, the boundaries between drugs and crime blur, thus revealing the complex and intimate relationship that links these two behaviors.
This book includes online access at www.jblearning.com, please refer library staff for the password.
Includes bibliographical references and index.
Keywords: Drug abuse and crime -- United States; Drug abuse -- United States -- Prevention; Crime prevention -- United States; Substance-Related Disorders